Muhammadiyah Boarding School (MBS) As A Pioneer Effort For An Educational Institution For Ulama Cadres - Ibnu Habibi; Tobroni Tobroni; Triyo Supriyatno; Ahmad Barizi; Salman Al Farisi (At-Ta'dib, 2024)
The aim of this research is to analyze the efforts of the Muhammadiyah Boarding School (MBS) Al Amin Bojonegoro Islamic Boarding School in developing the education of ulama cadres, the concept of ulama according to the pesantren's perspective, and the strategies implemented by the pesantren in producing Muhammadiyah ulama cadres This type of research uses a descriptive qualitative method with a case study approach. Data collection techniques are carried out through observation, interviews, and documentation. Data validity is checked through triangulation of sources and methods Data  analysis includes: data condensation, data   presentation, verification, and drawing conclusions The results of the study show: The concept of ulama at pesantren. MBS Al Amin Bojonegoro has the nature of tafaqquh fiddiin which means the ability to understand Islam, have memorized the Qur'an and can convey religious knowledge through lectures and sermons in the community. Learning in this pesantren is provided through madrasah diniyah and formal learning in madrasah schools, so that tafaqquh fiddiin includes mastery of religious knowledge and general knowledge. The steps taken by Islamic boarding schools in the formation of ulama cadre education includ: (a) Education and training through formalaaeducational institutions (schools/madrasahs) that are integrated with religious lessons; (b) Strengthening and accelerating memorization of the Qur'an with special training programs for tahsin, tamrin, and tasmik; (c) Habituation of student activities where activities are arranged for 24 hours which include ulama activities such as tahajud prayer, sunnah prayer, memorization activities, and diniyah lessons; (d) Developing and executing an integrated curriculum between the pesantren curriculum and the national